Vaccination and rheumatoid arthritis: an updated systematic review and meta-analysis of data from 25,949,597 participants - Pan, Hejing; Yu, Yin; Li, Xuanlin; Wang, Meijiao; Wen, Chengping; Dai, Qiaoding; Huang, Lin (BMC public health, 2025)
Objectives This systematic review and meta-analysis aimed to investigate the association between vaccinations and the risk of rheumatoid arthritis (RA), specifically addressing concerns about a potential increased risk among vaccinated individuals. Methods A systematic search for cohort studies and case-control studies examining the association between vaccinations and RA was conducted using Medical Subject Headings and relevant keywords across PubMed, EMBASE, and Cochrane Library databases from inception to September 2024. The risk of bias of included studies was assessed using the Newcastle-Ottawa Scale. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system was employed to evaluate the overall certainty of evidence. Statistical analyses, i.e., pooling of relative risk (RR) and corresponding 95% confidence intervals (CI), were performed using a random-effects model on STATA software (version 14.0). Due to the I² value exceeding 50%, we did not perform an asymmetry test to assess publication bias. Results This meta-analysis included 16 observational studies conducted between 2008 and 2024 and involving a total of 25,949,597 participants. The follow-up duration ranged from 0.03 to 9 years, while the data collection period varied from 2.75 to 9.5 years. The analysis found no significant association between vaccination exposure and RA [RR = 1.03, 95% CI (0.95–1.11), I²=93.4%, P = 0.456, low level of evidence]. Sensitivity analyses confirmed the robustness of this result. Subgroup analyses revealed no significant risk of RA associated with HPV vaccination [RR = 1.27 95% CI (0.78–2.08), I²=81.4%, P = 0.339], influenza vaccination [RR = 1.10, 95% CI (0.98–1.23), I²=52.4%, P = 0.112], Anthrax vaccination [RR = 2.21, 95% CI (0.75–6.52)], Herpes Zoster vaccination [RR = 2.70, 95% CI (1.70–4.29)], or COVID-19 vaccination [RR = 0.94, 95% CI (0.82–1.07), I²=97.4%, P = 0.340]. However, the subgroup with a follow-up duration varying between 0.5 and 1.8 years showed that (HPV & COVID-19) vaccination had a significant protective effect on RA [RR = 0.92, 95% CI (0.87–0.98), I²=95.3%, P = 0.005]. Conclusion The evidence for the association between vaccination and RA risk is insufficient, and vaccination may serve as a protective factor for RA over a less than one year follow-up duration.